TEACHERS’ PERCEPTION ABOUT TEACHING ENGLISH AT DIGITAL AGE TO YOUNG LEARNERS AT ELEMENTARY SCHOOLS IN PALANGKA RAYA - Stefhany, Awelma; Usadiati, Wahyuningsih; Misrita, Misrita (Journal Compound: Improving the Quality of English Education, 2021)
Teaching English to young learners might be of importance as they are in their golden age; their brains are still flexible so that they are able to learn anything, including language. The objective of the survey research was to find out teachers’ perceptions about the teaching of English to young learners at Elementary Schools in Palangka Raya at digital age 2020/ 2021.The research subjects were five English teachers at Elementary Schools in Palangka Raya. The research instruments were developed in the form of interview and a questionnaire using Google form for collecting the data needed. Description and quantitative were employed to expose the survey results. The results of the study were used to determine the perceptions/opinions of teachers about teaching English to young learners at elementary schools during the covid 19 pandemic in Palangka Raya, Central Kalimantan.